Some open challenges in polymer physics*. Issue 5 (9th March 2022) - McKenna, Gregory B.; Chen, Dongjie; Mangalara, Satish Chandra Hari; Kong, Dejie; Banik, Sourya
Abstract: Three subjects in polymer and soft matter physics are outlined in the present article. The first relates to concepts of an ideal glass transition. We describe work on ultra‐stable glass, either a 20‐million‐year‐old amber or a vapor deposited amorphous fluoropolymer, which examines the temperature dependence of the dynamics in a window between a low fictive temperature and the glass transition temperature. From this "finesse" of the problem of the geological time scales in sub‐glass temperature systems strong evidence that the divergence of the relaxation times at finite temperature from WLF‐types of extrapolation is not correct. The second topic is polymer nonlinear viscoelasticity as it relates to dynamic heterogeneity. We show results from mechanical hole burning experiments that suggest that dynamic heterogeneity arises from the nature of specific relaxation mechanisms rather than heterogeneous changes in, for example, the fictive temperature. Included is a discussion of large amplitude oscillatory shear testing and how it relates to characterization of nonlinear viscoelastic materials. The last topic addressed is the rheology of circular macromolecules. Here, we take a historical perspective and describe important new results from several laboratories that seem inconsistent. New works from our own studies on circular DNA are also discussed. Abstract :